(untitled) (Management and Connections Journal, 2021)
Organizational behaviors that are seen by society as negative can be analyzed within the concept of the Dark Side of Organizations, which studies issues that are traditionally forgotten, ignored or suppressed in Organizational Studies. However, the effects of organizational practices on non-human animals have not been included in this field of study, only indirectly when analyzing impacts on nature. At the same time, there is a growing social demand for moral consideration for non-human animals. This paper analyzes the communication strategies of the biggest brands in the meat and milk industry to respond to these demands, in addition to interviews with members of legislative, inspection and animal welfare training organizations. We concluded that the Dark Side should include the treatment given to non-human animals, since there is this demand from society and that the companies surveyed try to hide and / or distort reality.